2010
DOI: 10.1016/j.eurpsy.2009.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Duration and adherence of antidepressant treatment (2003 to 2007) based on prescription database

Abstract: Only one out of five patients complied with treatment for over four months. Treatment periods were shorter in men. In chronic processes, patients receiving polypharmacy presented the best compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
61
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 21 publications
12
61
1
2
Order By: Relevance
“…8 Data from the present study suggest better adherence to treatment than in three recent reports using comparable routine care data from England, 2 Spain, 15 and the US. 16 In contrast to at least one of these studies, 15 the present study found no clinically important difference in duration of treatment between males and females, and little difference between first-ever and subsequent treatment, suggesting a consistent approach to prescribing by GPs. By looking at population rather than individual case characteristics, it was not possible to ascertain what personal features, such as attitudes and beliefs, are associated with continuation, although these have been examined elsewhere.…”
Section: Comparison With Existing Literaturecontrasting
confidence: 52%
“…8 Data from the present study suggest better adherence to treatment than in three recent reports using comparable routine care data from England, 2 Spain, 15 and the US. 16 In contrast to at least one of these studies, 15 the present study found no clinically important difference in duration of treatment between males and females, and little difference between first-ever and subsequent treatment, suggesting a consistent approach to prescribing by GPs. By looking at population rather than individual case characteristics, it was not possible to ascertain what personal features, such as attitudes and beliefs, are associated with continuation, although these have been examined elsewhere.…”
Section: Comparison With Existing Literaturecontrasting
confidence: 52%
“…15 Several studies have reported no benefit for short-term antidepressant therapy in the treatment of depression, but less is known about the effects on pain. 16,17 Short-term antidepressant therapy may be an indicator for non-adherence 16 to this medication and increased reliance on riskier medications for pain management. Alternatively, in an analysis of root causes of opioid overdose deaths, Webster and colleagues suggested that antidepressant use could pose risks due to central nervous system depressant effects, and recommended structured care for persons with mental health disorders who are treated with opioids for pain.…”
Section: Discussionmentioning
confidence: 99%
“…[28,29] The MPR is considered acceptable if the calculated value is ≥80% but ≤110%. [14] An MPR of <80% indicates the presence of refill gaps, so that possession is considered unacceptably low (undersupply), whereas an MPR >110% is considered unacceptably high (oversupply). Data management and analysis were performed using SAS Version 9.1.3 (SAS Institute, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The MPR is a well-established method of calculating drug compliance in pharmcoepidemiological studies, including chronic diseases such as depression, [14] hypertension [25] osteoporosis [26] and schizophrenia. [27] However, it is important to note that the compliance value obtained from the MPR only gives an indication of the possession of medicine by the patient, and that appropriate consumption of medicine is assumed to ensue from possession.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation